Manuscript Evidence of the Genesis of Sermons by Peter of Zittau - Pumprová, Anna (Medieval sermon studies, 2019)
The article deals with the sermon collection entitled Sermones de principalibus festis, by Peter of Zittau (d. 1339). The collection has survived in a single manuscript - codex Ms 434 at Leipzig University Library. Drawing on the results of paleographic, codicological and textual analysis of codex Ms 434, the authors explore what the manuscript record of the sermons reveals about the genesis of the texts and Peter of Zittau's working methods. Particular attention is paid to the numerous corrections which were added to the text of the sermons (as copied into the codex by a scribe) by a different contemporary hand. Based on an analysis of the nature of these corrections and a comparison of the handwriting with that of Peter of Zittau (as known from the autograph of the second book of his Chronica Aulae regiae), the paper tests the hypothesis that the author of the corrections in manuscript Ms 434 was Peter of Zittau himself.